OPTIMIZING SHARIA INVESTMENT POLICY BASED ON FINANCIAL TECHNOLOGY (FINTECH) TO SUPPORT AN INCLUSIVE DIGITAL ECONOMY - Said, Muhammad; Madi, Minhajuddin; SR, Naharuddin.; Hajrawati, Hajrawati; Taufiq, Muh. (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2025)
The development of sharia-compliant financial technology (fintech) hasemerged as a key driver of financial inclusion in Indonesia, yet low shariafinancial literacy and digital infrastructure disparities hinder its potential tofoster an inclusive digital economy. This study aims to formulate strategies foroptimizing sharia investment policies based on fintech to enhance access tosharia-compliant financial services and support a just digital economy.Employing a library research method with a content analysis approach, this studyexamines literature from Scopus-indexed journals, OJK reports, and DSN-MUIfatwas to identify patterns, trends, and policy gaps. The findings reveal thatsharia fintech expands financial access through platforms such as peer-to-peerlending and digital payments, with sharia financing reaching IDR 585.46 trillionin 2023, predominantly through musyarakah and murabahah contracts. However,challenges such as a sharia financial literacy rate of only 12.1%, uneven digitalinfrastructure, and insufficiently adaptive regulations limit inclusivity. The studyconcludes that data-driven, integrated policies and cross-sectoral collaborationare essential to overcome these barriers. Recommendations include strengtheningadaptive regulations by OJK, enhancing digital literacy through communitybased campaigns, and developing digital infrastructure in remote areas to ensurethe benefits of the digital economy are equitably distributed.